FUNGSI KERUKUNAN KELUARGA KALANG (K3) DALAM ASPEK SOSIAL EKONOMI (KASUS DI DESA AMBALKEBREK KEBUMEN) (Solidarity: Journal of Education, Society and Culture, 2012)
Kalang society is no longer identical to the shape of the house and rituals that symbolizes nobility. Kalang should complement its traditional institutions with modern ones to cope with the increasingly complex situation of the modern world. Kalang community in Ambalkebrek have modern ideas by forming K3 (prop family harmony) which have an impact on new relationships in the community. K3 and society in the social aspect is open to the members of the K3 is the head of the village, and the presence of family Kalang (K3) is honored with a title nganten. K3 and society in the economic aspects of cooperation, in running a business entrepreneur K3 employ many local people. The method used in this study is qualitative research methods. The focus of research is the function of K3 in social economic relations in Ambalkebrek Ambal Kebumen.